The IRAN’S NUCLEAR PROGRAM AND ITS IMPACT ON MIDDLE EASTERN REGIONAL SECURITY IN THE 2020–2024 PERIOD - Saputra, Rafli Adi; Hapsari, Renitha Dwi (Universitas KH. Abdul Chalim Mojokerto, 2026)
Iran's nuclear program has become a strategic issue influencing the security architecture of the Middle East, particularly during the 2020–2024 period. Since the United States withdrew from the Joint Comprehensive Plan of Action (JCPOA) in 2018, Iran’s nuclear development has continued to create new tensions with regional states, particularly Israel, Saudi Arabia, and the United Arab Emirates. This research aims to analyze the impact of Iran's nuclear program on regional security in the Middle East using the framework of the Regional Security Complex Theory (RSCT), which emphasizes the interconnection among states within a conflict-prone region. The research employs a qualitative method with a descriptive-analytical approach, relying on literature studies from academic journals, international organizations’ reports, and official documents from governments and international institutions. The findings indicate that Iran’s nuclear program not only exacerbates regional instability but also encourages the formation of new alliances, such as the normalization of relations between Israel and Gulf states through the Abraham Accords. Moreover, the nuclear issue further reinforces the rivalry between the pro-Iran bloc and the pro-West bloc, which has implications for the consolidation of regional defense strategies. Therefore, Iran’s nuclear program serves as a key factor in shaping the direction and prospects of Middle Eastern regional security during the 2020–2024 period. Keywords: Iran, Nuclear Program, Regional Security, Regional Security Complex, Middle East